Advances and challenges in the treatment of primary central nervous system lymphoma. Issue 12 (18th May 2020) - Yang, Hua; Xun, Yang; Yang, Anping; Liu, Fang; You, Hua
Abstract: Primary central nervous system lymphoma (PCNSL), a rare variant of non‐Hodgkin's lymphoma, is characterized by distinct biological characteristics and clinical behaviors, and patient prognosis is not satisfactory. The advent of high‐dose (HD) methotrexate (HD‐MTX) therapy has significantly improved PCNSL prognosis. Currently, HD‐MTX‐based chemotherapy regimens are recognized as first‐line treatment. PCNSL is sensitive to radiotherapy, and whole‐brain radiotherapy (WBRT) can consolidate response to chemotherapy; however, WBRT‐associated delayed neurotoxicity leads to neurocognitive impairment, especially in elderly patients. Other effective approaches include rituximab, temozolomide, and autologous stem‐cell transplantation (ASCT). In addition, new drugs against PCNSL such as those targeting the B‐cell receptor signaling pathway, are undergoing clinical trials. However, optimal therapeutic approaches in PCNSL remain undefined. This review provides an overview of advances in surgical approaches, induction chemotherapy, radiotherapy, ASCT, salvage treatments, and novel therapeutic approaches in immunocompetent patients with PCNSL in the past 5 years. Additionally, therapeutic progress in elderly patients and in those with relapsed/refractory PCNSL is also summarized based on the outcomes of recent clinical studies. Abstract : This review provides an overview of advances in surgical approaches, induction chemotherapy, radiotherapy, autologous stem‐cell transplantation, salvage treatments, and novel therapeutic approaches in immunocompetent patients with primary central nervous system lymphoma (PCNSL) in the past 5 years. Additionally, therapeutic progress in elderly patients and in those with relapsed/refractory PCNSL is also summarized based on the outcomes of recent clinical studies.